Pregnancy in past or present lupus nephritis: a study of 32 pregnancies from a single centre. Issue 6 (1st June 2001) - Huong, D Lê Thi; Wechsler, B; Vauthier-Brouzes, D; Beaufils, H; Lefebvre, G; Piette, J-C
Abstract : OBJECTIVE: To study maternal and fetal outcome in women with past or present histologically proven systemic lupus erythematosus (SLE) nephritis. METHOD: Retrospective study of 32 pregnancies in 22 women with past or present histologically proven SLE nephritis in a single French centre. RESULTS: Pregnancy (25 planned and 7 not planned) occurred in a mean (SD) of 8 (5) years after SLE diagnosis and 6 (4) years after renal disease onset. Seven occurred in women with antiphospholipid syndrome. At pregnancy onset, all but one woman had creatininaemia below 100 μmol/l, five had proteinuria >0.5 g/day, none had hypertension. Twelve pregnancies occurred in women previously treated with immunosuppressant drugs. Treatment comprised prednisone (n=31), hydroxychloroquine (n=11), aspirin (n=22), heparin (n=12), and azathioprine in one patient with steroid resistant nephrotic syndrome disclosing SLE. No therapeutic abortion was done. During pregnancy or the postpartum period, or both, proteinuria >0.5 g/day occurred in 10 women (five related to pre-eclampsia, four to renal flare, one to stable nephrotic syndrome). One flare consisted of mild arthralgias. Pregnancy outcome comprised one feto-maternal death in SLE disclosed by pregnancy, five embryonic losses, two fetal deaths, and 18 premature (one neonatal death) and six full term births. No criterion appeared to influence fetal survival significantly. At long term, one patient died during an SLE flare, three women had renal relapses. At the last visit, all had creatininaemia below 100 μmol/l except one woman with creatinine level 115 μmol/l, nine had proteinuria >0.5 g/day, and one was treated for hypertension. CONCLUSION: Pregnancy need not be discouraged in women with a history of SLE nephritis with normal or mildly impaired renal function. Deterioration of renal function rarely occurs. However, these pregnancies are at high risk of pre-eclampsia and prematurity.